Oxazolopyridines and thiazolopyridines as monoamine oxidase B inhibitors for the treatment of Parkinson's disease - Park, Hye Ri; Kim, Jiyoon; Kim, Taekeun; Jo, Seonmi; Yeom, Miyoung; Moon, Bongjin; Choo, Il Han; Lee, Jaeick; Lim, Eun Jeong; Park, Ki Duk; Min, Sun-Joon; Nam, Ghilsoo; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In Parkinson's disease, the motor impairments are mainly caused by the death of dopaminergic neurons. Among the enzymes which are involved in the biosynthesis and catabolism of dopamine, monoamine oxidase B (MAO-B) has been a therapeutic target of Parkinson's disease. However, due to the undesirable adverse effects, development of alternative MAO-B inhibitors with greater optimal therapeutic potential towards Parkinson's disease is urgently required. In this study, we designed and synthesized the oxazolopyridine and thiazolopyridine derivatives, and biologically evaluated their inhibitory activities against MAO-B. Structure-activity relationship study revealed that the piperidino group was the best choice for the R-1 amino substituent to the oxazolopyridine core structure and the activities of the oxazolopyridines with various phenyl rings were between 267.1 and 889.5 nM in IC50 values. Interestingly, by replacement of the core structure from oxazolopyrine to thiazolopyridine, the activities were significantly improved and the compound in with the thiazolopyridine core structure showed the most potent activity with the IC50 value of 26.5 nM. Molecular docking study showed that van der Waals interaction in the human MAO-B active site could explain the enhanced inhibitory activities of thiazolopyridine derivatives. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: BRAIN ASTROCYTES; DOUBLE-BLIND; RASAGILINE; SELEGILINE